Ritus Ngunduh Patirtan Jolotundo Sebagai Sistem Konservasi Air Berbasis Kearifan Lokal Mojokerto dan Urgensinya Sebagai Warisan Budaya Tak Benda - Rakhmad Saiful Ramadhani; Masnia Ningsih; Jenny Yudha Utama (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article analyzes the Ngunduh Patirtan Jolotundo ritual as a community-based water conservation system rooted in local wisdom in Mojokerto Regency, and examines its potential as the academic basis for a Regent’s Regulation on Intangible Cultural Heritage (ICH) designation. The study employs a normative-empirical approach integrating literature review, field study, juridical analysis of regulatory hierarchies, and comparative analysis with similar ICH practices across Indonesia. The Ngunduh Patirtan ritual effectively functions as a communal water conservation mechanism through its procession of collecting water from 33 springs on Mount Penanggungan. The tradition possesses robust philosophical, sociological, and juridical foundations for designation as Mojokerto’s ICH. This is the first study to systematically integrate the spiritual-ecological, legal, and public policy dimensions of the Ngunduh Patirtan tradition into a unified analytical framework as a basis for local regulation.